Generation of Skin Organoids: Potential Opportunities and Challenges - Sun, Hui; Zhang, Yi-Xuan; Li, Yu-Mei (Frontiers in Cell and Developmental Biology, 2021)
Although several types of human skin substitutes are currently available, they usually do not include important skin appendages such as hair follicles and sweat glands, or various skin-related cells, such as dermal adipocytes and sensory neurons. This highlights the need to improve the in vitro human skin generation model for use as a tool for investigating skin diseases and as a source of cells or tissues for skin regeneration. Skin organoids are generated from stem cells and are expected to possess the complexity and function of natural skin. Here, we summarize the current literatures relating to the ‘niches’ of the local skin stem cell microenvironment and the formation of skin organoids, and then discuss the opportunities and challenges associated with multifunctional skin organoids.